Educação especial: análise e caracterização das salas de recursos multifuncionais no ensino fundamental 1 no município de Aracruz- Espírito Santo - Crescencio, Renato (2019)
Introduction: National guidelines on inclusive education are well established in the official documents dealing with the subject. However, it is necessary for municipalities to develop strategies to meet this demand. The ESA may be offered by public education systems or specialized institutions, with the Multifunctional Resource Room (SRM), as a priority area equipped with equipment, furniture, didactic and pedagogical materials, for the ESA offer. Objective: Documentary analysis of the data related to the schooling of the target public students of Special Education and characterization of multifunctional resource rooms (SRM) of elementary education 1 of the public network in the city of Aracruz / Espirito Santo. Method: The first part of the paper focused on documentary and bibliographical research, based on the analysis of scientific articles, books, researches already done on the subject and collection of statistical data. The second was the field work characterized by a visit to 6 polo schools of the 24 existing in the municipality of Aracruz and analysis of the documentation folders of the 50 students. Sample: We analyzed documents of 50 students, selected from 154 elementary students 1, enrolled in the Multifunctional Resource Rooms (SRM) in the year 2017. Results: the proposal of specialized educational service in elementary education in the municipality of Aracruz no Espirito Santo is based on the guidelines of the Ministry of Education and current legislation. The documentation of the students enrolled allows to know the condition of the disability, but does not allow the teacher, to establish a link between the planning of teaching and the particularities of the student with a disability. AEE offered in SRM was considered to be relevant to the process of inclusion of students in school, the target audience of special education, although it presented some difficulties regarding its organization and functioning. Final considerations: The result presented in this study made it possible to identify that the inclusion policy in the municipality of Aracruz, through the multifunctional resources rooms, found in the municipal schools visited, is in the process of structuring and in the right direction.